1998
DOI: 10.2337/diabetes.47.10.1602
|View full text |Cite
|
Sign up to set email alerts
|

Ciliary neurotrophic factor potentiates the beta-cell inhibitory effect of IL-1beta in rat pancreatic islets associated with increased nitric oxide synthesis and increased expression of inducible nitric oxide synthase.

Abstract: Proinflammatory cytokines are implicated as effector molecules in the pathogenesis of IDDM. Interleukin-6 (IL-6) alone or in combination with IL-1beta inhibits glucose-stimulated insulin release from isolated rat pancreatic islets by unknown mechanisms. Here we investigated 1) if the effects of IL-6 are mimicked by ciliary neurotrophic factor (CNTF), another member of the IL-6 family of cytokines signaling via gp130, 2) the possible cellular mechanisms for these effects, and 3) if islet endocrine cells are a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 0 publications
4
27
0
2
Order By: Relevance
“…We found that alloxan disrupts, whereas CNTF impairs, GSIS, in accordance with the literature and with results from our group [13,14,26]. The novelty here is that CNTF partially recovers GSIS in pancreatic islets from alloxan-treated mice.…”
Section: Discussionsupporting
confidence: 82%
“…We found that alloxan disrupts, whereas CNTF impairs, GSIS, in accordance with the literature and with results from our group [13,14,26]. The novelty here is that CNTF partially recovers GSIS in pancreatic islets from alloxan-treated mice.…”
Section: Discussionsupporting
confidence: 82%
“…It has been suggested that CNTF, released from destroyed b-cells during the inflammatory process that occurs during the onset of type 1 diabetes, may act as a proinflammatory cytokine by potentiating the action of IL-1b on b-cells (Wadt et al 1998). However, to date, CNTF, in contrast to IL-6 (Ahima 2006) has not yet been tested as a differentiation and/ or survival factor in pancreatic islets.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, CNTF expression has already been identified in b-cells (Wadt et al 1998). For these reasons, we decided to study the possible effects of CNTF on rat pancreatic islets differentiation and/or survival.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression levels of Gadd45a, Gadd45b and Gadd45g were calculated by the standard curve method and the quantity of each cDNA was normalised for transcription factor Sp-1, showing no regulation by IL-1β [25]. The primers were as follows: Gadd45a, 5′-TGAGCTGCTGC TACTGGAGA-3′ and 5′-TGTGAT GAATGTGGGTTCGT -3′; Gadd45b, 5′-ATTGACATCG TCCGGGTATC-3′ and 5′-TGACAGTTCGTGACCAGG AG-3′; Gadd45g, 5′-GC ATCCTCATTTCGAATCCT-3′ and 5'-CACCCAGTCGTT GAAGCTG-3′; Sp-1, 5′-GG CTACCCCTACCTCAAAGG -3′ and 5′-CA CAACAT ACTGCCCACCAG-3′.…”
Section: Quantitative Rt-pcrmentioning
confidence: 99%